Determinants Factors of Microfinance Performance in Nepal - Chaulagain, Krishna Prasad; Lamichhane, Basu Dev (Journal of Nepalese Business Studies, 2022)
This study concerns the key factors of performance of the Nepalese microfinance institutions (MFIs). The principal goal of the study is the identification of necessary operational performance of MFIs. The determinants influencing MFIs' performance were identified using descriptive, correlational, and casual-comparative study methodologies. The study's conclusions demonstrated a strong correlation between MFIs performance and information technology, loan lending processes, and regulatory environment. The regulatory Framework seems to be an important factor in Nepal's microfinance performance as well. The study also discovered that MFIs performance is significantly influenced by the loan lending system, regulatory environment, and information technology. The study discovered that the loan lending system, regulatory framework, information technology, loan lending system, employee motivation, management system, effective risk management, and regulatory framework have a positive link with the performance of MFIs and significantly affect it. Additionally, it shows that the operational effectiveness of MFIs in Nepal has no correlation with employee motivation, management system, and effective risk management. The study's findings will be helpful to all parties involved with MFIs, including investors, regulators, legislators, and BFIs. According to the outcome, operational efficiency significantly affects the viability and continuation of service of Nepalese MFIs.